2016
DOI: 10.1002/ijch.201600025
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)‐Dioxygen Adducts and Copper Enzyme Mechanisms

Abstract: Primary copper(I)-dioxygen (O2) adducts, cupric-superoxide complexes, have been proposed intermediates in copper-containing dioxygen-activating monooxygenase and oxidase enzymes. Here, mechanisms of C–H activation by reactive copper-(di)oxygen intermediates are discussed, with an emphasis on cupric-superoxide species. Over the past 25 years, many synthetically derived cupric-superoxide model complexes have been reported. Due to the thermal instability of these intermediates, early studies focused on increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 95 publications
(238 reference statements)
2
79
0
Order By: Relevance
“…While LPMOs have been studied less than other copper-containing monooxygenases, enzymatic and computational studies have led to the proposals of reaction mechanisms which may be similar to those suggested for PHM, DβM, and TβM; however, other possibilities exist [17, 77, 8082]. Possible copper-(di)oxygen intermediates involved in HAT from substrate are shown in Fig.…”
Section: Single Copper Active Sitesmentioning
confidence: 96%
See 4 more Smart Citations
“…While LPMOs have been studied less than other copper-containing monooxygenases, enzymatic and computational studies have led to the proposals of reaction mechanisms which may be similar to those suggested for PHM, DβM, and TβM; however, other possibilities exist [17, 77, 8082]. Possible copper-(di)oxygen intermediates involved in HAT from substrate are shown in Fig.…”
Section: Single Copper Active Sitesmentioning
confidence: 96%
“…Reduction of O 2 using copper complexes and the subsequent reactivity of the resultant intermediates have both been widely studied [1317]. Many different Cu n O 2 intermediates can be formed and have been extensively investigated in terms of spectroscopy and reactivity (Fig.…”
Section: Structurally Characterized Copper-dioxygen Speciesmentioning
confidence: 99%
See 3 more Smart Citations